2019
DOI: 10.1177/0894845319853385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Career Exploration Intervention on Students’ Career Maturity and Self-Concept

Abstract: This study investigated the effects of a career exploration intervention (CEI) on career maturity and self-concept among Malaysian high school students, using a true experimental design (pretest–posttest with a control group). One hundred thirty-nine high school students in Malaysia were recruited and randomly assigned to receive either a CEI or no intervention. Multivariate analyses of covariance showed significant differences in career maturity and self-concept between the experimental and control groups. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
1
33
0
5
Order By: Relevance
“…Another factor that creates low career maturity of students is that most of the students with special needs do not know planning and job that they have to choose after graduates, they have difficulty making decisions and are not sure about their careers, causing their careers to be immature. This statement is in line with previous research showing that adolescent students have a low level of career maturity (Lau et al, 2019;Saifuddin et al, 2017). Moreover, previous research showed that in the industrial world, children with special needs are more likely to be unemployed, experiencing discrimination, being unemployed more often, and getting lower wages (Dispenza, 2019;Lombardi et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Another factor that creates low career maturity of students is that most of the students with special needs do not know planning and job that they have to choose after graduates, they have difficulty making decisions and are not sure about their careers, causing their careers to be immature. This statement is in line with previous research showing that adolescent students have a low level of career maturity (Lau et al, 2019;Saifuddin et al, 2017). Moreover, previous research showed that in the industrial world, children with special needs are more likely to be unemployed, experiencing discrimination, being unemployed more often, and getting lower wages (Dispenza, 2019;Lombardi et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Previous research by Fitriyah et al (2018) and Novitarani & Wahyuno (2018) career guidance services for vocational students were carried out well and could increase students' career maturity. Students in Asia benefit from career guidance through career counselling services (Lau et al, 2019). The implementation of counselling guidance for students with special needs can be done by developing teaching materials in the form of modules (Bancin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that CM was not affected is not surprising as because of their youth, participants had probably not yet developed career maturity and concerning motivation (Lau, Chung, & Wang, 2019). SE and creativity were affected by our creative STEAM instruction.…”
Section: Resultsmentioning
confidence: 85%
“…Jika dihubungkan dengan teori pemilihan pekerjaan yang menyebutkan diperlukannya sebuah keseimbangan antara diri seseorang dengan lingkungan dalam proses pemilihan pekerjaan dan karier, eksplorasi karier memegang peran penting dalam penentuan seseorang dalam memilih pekerjaannya (Chan, 2018;Modestino et al, 2019;Zikic & Hall, 2009). Perilaku eksplorasi karier juga akan membentuk sikap (Jiang et al, 2019), merencanakan karier di masa mendatang (Demulier et al, 2013), dan mematangkan karier yang dimiliki seseorang (Lau et al, 2019).…”
Section: Pendahuluanunclassified